Progressively analogous evidence of covert face recognition from functional magnetic resonance imaging and skin conductance responses studies involving a patient with dissociative amnesia. (16th August 2018) - Chechko, Natalya; Stickel, Susanne; Kellermann, Thilo; Kirner, Andre; Habel, Ute; Fernández, Guillén; Schneider, Frank; Kohn, Nils
Abstract: This is a case study involving a female patient (NN) with complete loss of autobiographical memory and identity despite normal neurological assessment. To test the hypothesis that patients with dissociative amnesia (DA) possess the ability to covertly process facial identities they are unaware of, we conducted functional magnetic resonance imaging (fMRI) and assessed skin conductance responses (SCR) to (a) strangers, (b) celebrities, and (c) familiar faces not seen since the onset of DA. We also performed associative face‐name memory tasks to test the patient's ability to learn and recall newly learned face‐name pairs. Although NN did not recognize any of the faces of her friends and relatives, their images triggered a stronger involvement of the left fusiform gyrus, the bilateral hippocampus/amygdala region, the orbitofrontal cortex, the middle temporal regions, and the precuneus, along with higher SCR. During recollection of previously learned face‐name pairs, NN (compared to healthy controls) demonstrated a weaker involvement of the hippocampus. Our findings suggest that, in DA, specific arousal systems remain capable of being activated by familiar faces outside of conscious awareness. The decreased activation observed in the hippocampus demonstrates that the functioning of memory‐sensitive regions may be impaired by trauma. Abstract : We examined a patient with dissociative amnesia (DA) to assess her capability with respect to the covert processing of facial identity of friends/relatives. The faces triggered the recruitment of the face‐processing network, the bilateral hippocampus/amygdala, the orbitofrontal cortex, and the bilateral temporal gyri, along with a higher skin conductance response. We suggest that, in DA, specific arousal systems remain capable of being activated by familiar faces outside of conscious awareness.